1978
DOI: 10.1136/jmg.15.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 8 syndrome.

Abstract: Clinical and dermatoglyphic data on a male patient with complete trisomy 8 are reported and compared with those of other known cases of trisomy 8. The more discriminating findings for this condition are skeletal anomalies, restricted articular function, and speech problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
6
0
1
Order By: Relevance
“…A review of the published reports shows that there are great variations in the clinical manifestations of regular trisomy 8 cases [1,4,9]. Our case has many features in common with the previously reported cases, among those are skeletal anomalies, restricted articular functions, low-set ears, microretrognathia, motor retardation, hypospadias and bilateral undescended testes and small penis [2,3], and speech problems.…”
Section: Discussionsupporting
confidence: 64%
“…A review of the published reports shows that there are great variations in the clinical manifestations of regular trisomy 8 cases [1,4,9]. Our case has many features in common with the previously reported cases, among those are skeletal anomalies, restricted articular functions, low-set ears, microretrognathia, motor retardation, hypospadias and bilateral undescended testes and small penis [2,3], and speech problems.…”
Section: Discussionsupporting
confidence: 64%
“…Sin embargo, reconocen que estas características suelen encontrarse también en otras patologías por lo que recomiendan el estudio citogenético y el establecimiento de un diagnóstico diferencial con otras condiciones como el síndrome de Fong, la artrogriposis y el síndrome oto-palato-digital 7 Fineman et al, en 1975 establece que la trisomía 8 pura (T8) y la trisomía 8 en mosaico (T8m) son dos entidades diferentes pues identifica comparando sus hallazgos con los de otros 17 pacientes de una densa opacidad corneal y la deformidad clavicular como dos características solo presentes en la T8m 8 . Gagliardi describe el caso de un individuo de 21 años, con deformidades esqueléticas a nivel de tronco (cifoescoliosis) y extremidades (malrotación articular y genu valgus) y una osteosporosis generalizada, en quien a partir de cultivo de médula ósea se encontró un complemento cromosómico de 47,XY,+C identificándose el cromosoma extra como un miembro del par 8 por bandas GTG, a pesar de determinarse una T8 pura no hubo evidencias de retraso mental, lo que demuestra la gran variabilidad fenotípica existente en esta condición 9 .…”
Section: Discussionunclassified
“…Although they do not indicate the presence of muscular atrophy, the photographs illustrate this feature. Gagliardi et al [1978] described a dysmorphic adult male patient with typical facial features, progeroid appearance, FTT, absence of pubertal development, and multiple congenital anomalies. Hendson et al [2003] described an infant with characteristic facial features, FTT, wasted appearance, and multiple congenital anomalies (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…In live births, T8 is thought to almost always be associated with mosaicism. Nonmosaic or T8 syndrome is rare postnatally having only been described a few times in living individuals [Lejeune et al, 1969;Gagliardi et al, 1978;Hendson et al, 2003]. The estimated frequency of trisomy 8 mosaicism (T8M), also known as Warkany syndrome [Warkany et al, 1962], is about 1/25,000 to 50,000 liveborns, and is found to be more prevalent in males than females, 5:1 [Gorlin et al, 2001].…”
Section: Introductionmentioning
confidence: 99%